Incorporating Humor As A Strategy In Teaching Speaking At Indonesian EFL Classroom - Iin Sulastri Ode Ami; La Sunra; Nur Aeni (Hasanuddin University, 2023)
This research aims to explore the lecturer’s incorporation of humor in teaching speaking skills at Universitas Iqra Buru and to find out the constraints encountered by the lecturer in teaching speaking skills through humor at Universitas Iqra Buru.. This research applied the descriptive qualitative design. In the English education department, there were six lecturers, and then the researcher used a purposive sampling technique with criteria; the lecturers who taught speaking skills used humor strategies, so the researcher got one lecturer who met the requirements. Then, in the class where the lecturer taught, there were seventeen students. The research instruments were observation, interviews, and documentation. This research showed that the lecturer included humor in teaching speaking skills during learning, namely at the beginning of the lesson, then in the middle of the lesson, and at the end of the lesson. According to students, teaching using humor is very effective, comfortable, not stressful, eliminates anxiety, can understand the material presented by the lecturer, reduces stress and stiffness in receiving material, and keeps students focused.